HYDROACOUSTIC LOCATION OF AN OCEANIC EARTHQUAKE ORIGIN AREA - Lappo S.S.; Levin B.W.; Sassorova E.V.; Morozov V.E.; Didenkulov I.N.; Karlik Ya.S. (My University, 2003)
A joint analysis of the local Kamchatka earthquake catalogue data and hydro-acoustic measurements obtained during the Acoustic Thermometry of Ocean Climate (ATOC) experiment was carried out. The time series of acoustic records coincident with the earthquakes or measured immediately before the beginning of earthquakes were analyzed. Two types of signals were distinguished from the hydro acoustic records (HAR): the micro-earthquakes (MEQ) whose focuses were located in the same area as the seismic focus of the main EQ and a seismic noise, which starts before the main shock. The duration of a MEQ was about 3-4 seconds. The new method of the HAR data processing demonstrates the possibility of an oceanic earthquake origin location for a few minutes before the main shock hit.